Depth-Dependent Distribution of Nickel (Ni) and Silica (SiO2) in Laterite Nickel Ore - Aslan Ndita; Al Jalali Muhammad (Jurnal Aplikasi Fisika, 2025)
This study investigates the vertical distribution of nickel (Ni) and silica (SiO2) concentrations within soil profiles at depths ranging from 45 cm to 1600 cm. Soil samples were systematically collected and analyzed to determine their elemental composition. The results showed that the maximum Ni concentration of 1.15% was found at a depth of 1150 cm, while the lowest concentration of 0.21% occurred at 1600 cm. In contrast, the concentration of SiO2 increased with depth, reaching a peak of 44% at 1500 cm and the lowest value of 0.2% at 45 cm. These contrasting distribution patterns suggest different geochemical behaviors and mobility of Ni and SiO2, which are likely influenced by differential weathering intensity and mineralogical transformations within the soil horizons. The findings provide important insights into the geochemical processes affecting element partitioning in lateritic soil profiles and have significant implications for mineral exploration and environmental studies.